(untitled) (Research, Society and Development, 2021)
Flaked corn flour (FCF) is very present at the breakfeast, demarcating the Strong presence of corn on northeastern diet. The objective was evaluate the sanitary quality of the FCF marketed on Região da Grande Recife (RGR), trhough biological assays to investigation of petogenic microrganisms provided for in legislation of patogenics and deteriorating microsganisms. Were not detected the presence of enteropatogenic provided for in sanitary legislation, however, accompainyng microbiota was detected, such as mesophiles mold, yeast and termo-resistant fungi. Although the detection on those biological agentes, the concentration was conforming with the sanitary recomendation. However, the presence of microrganisms able to pruduce secondary metabolits, such as mycotoxins, may evolve into carcinogenic and hepatotoxic conditions mainly in vulnerable groups, what may provoke a great disorder at public health.